2021
DOI: 10.3389/fmed.2021.585358
|View full text |Cite
|
Sign up to set email alerts
|

Population Bottlenecks and Intra-host Evolution During Human-to-Human Transmission of SARS-CoV-2

Abstract: The emergence of the novel human coronavirus, SARS-CoV-2, causes a global COVID-19 (coronavirus disease 2019) pandemic. Here, we have characterized and compared viral populations of SARS-CoV-2 among COVID-19 patients within and across households. Our work showed an active viral replication activity in the human respiratory tract and the co-existence of genetically distinct viruses within the same host. The inter-host comparison among viral populations further revealed a narrow transmission bottleneck between p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 28 publications
3
23
0
Order By: Relevance
“…So far, efforts to understand how transmission shapes the evolution of SARS-CoV-2 have mainly focused on small household events or nosocomial pairs [3][4][5][6][7]. Such studies point to a narrow transmission bottleneck that significantly reduces viral genetic diversity at the start of each infection [3,4,[6][7][8]. While exact estimates of the bottleneck range from 1 to 15 virions, it is clear that a limited number of virions initiate most human infections.…”
Section: Introductionmentioning
confidence: 99%
“…So far, efforts to understand how transmission shapes the evolution of SARS-CoV-2 have mainly focused on small household events or nosocomial pairs [3][4][5][6][7]. Such studies point to a narrow transmission bottleneck that significantly reduces viral genetic diversity at the start of each infection [3,4,[6][7][8]. While exact estimates of the bottleneck range from 1 to 15 virions, it is clear that a limited number of virions initiate most human infections.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with this bottleneck, sequencing studies have provided conflicting results with respect to the ability of intrahost variants to transmit and establish new SARS-CoV-2 lineages that have the potential to transmit widely. While a number of studies have shown this to be the case [21][22][23][24] , other studies have not been able to demonstrate transmission of viral lineages derived from intrahost evolution 11,25,26 . The stochasticity in inter-host transmission of specific viral lineages is compounded by the overdispersed nature of SARS-CoV-2 spread, where most onward transmission originates from a small number of individuals.…”
mentioning
confidence: 99%
“…In the review there were 2 studies discussed the COVID 19 genotypes. The work of Ramaiah and Arumugaswami (2020) and of Wang et al 2021. The nCoV genotype have been evolved from a bat-CoV by accumulating non-synonymous mutations, indels, and recombination events.…”
Section: Resultsmentioning
confidence: 99%